2022
DOI: 10.1039/d2fo00021k
|View full text |Cite
|
Sign up to set email alerts
|

6,8-(1,3-Diaminoguanidine) luteolin and its Cr complex show hypoglycemic activities and alter intestinal microbiota composition in type 2 diabetes mice

Abstract: Flavonoid compounds such as luteolin exhibit hypolipidemic effects, and there are few reports on the hypoglycemic activity of luteolin derivatives. In this research, 6, 8-(1, 3-diaminoguanidine) luteolin (DAGL) and its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Therefore, it was indicated that the SVM could prevent the formation of free fatty acids by reducing the accumulation of fat, 40 which was consistent with the previous research. 41…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was indicated that the SVM could prevent the formation of free fatty acids by reducing the accumulation of fat, 40 which was consistent with the previous research. 41…”
Section: Resultsmentioning
confidence: 99%
“…Second, new compounds with obvious hypoglycemic effects may be obtained by structural modification of some natural products, which greatly expands the ideas of drug development. For example, 6,8-(1,3-diaminoguanidine) luteolin, a luteolin derivative, increased the abundance of Ruminiclostridium and decreased the abundance of Lachnoclostridium and Parabacteroides , thereby improving glucose metabolism in T2DM mice . Finally, given the complexity of host-gut microbiota crosstalk, elucidation of the molecular mechanisms underlying the protective effects of these natural products on DM is still a long way off.…”
Section: Future Perspectivementioning
confidence: 99%
“…We extracted genomic DNA from intestinal contents according to the method of Ge et al [ 68 ]. We amplified the V3−V4 region of the bacterial 16S rRNA gene using universal primers 338F and 806R.…”
Section: Methodsmentioning
confidence: 99%